THE DEVELOPMENT OF THE COMMUNICATIVE SKILLS OF THE FUTURE TEACHERS OF PRIMARY SCHOOLIN THE PROCESS OF TRAINING SOLUTION OF THE EDUCATIONAL SITUATIONS - Kilichenko, Oksana I. (Educological discourse, 2015)
The article considers the peculiarities of the development of the pedagogical communicative facilities of the future primary school teachers in the process of solution of the educational situations with the help of the professional and pedagogical training. The author defines context and coaching approaches which ought to be taking into consideration in the educational process during the organization of the professional and pedagogical training in the practical-laboratory seminars of the pedagogical disciplines. Educational situations must have the context character, the organization of the process of their solution must consider the coaching approach. The article analyses the essence and tasks of the professional and pedagogical training, characterizes the principles which ought to be considered in the process of its organization. The stages of the elaboration of the educational situations are defined.